2017
DOI: 10.1097/mph.0000000000000661
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Celiac Disease in Children With Arterial Ischemic Stroke

Abstract: In the present study, children with acute arterial stroke did not exhibit a higher prevalence rate of CD compared with healthy controls. Therefore, the screening test for CD is not a necessary part of the management of AIS in children. However, cases of recurrent AIS could be examined for CD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…The pathogenesis of stroke in CD youth may involve vitamin B12 deficiency[ 68 ] and possibly hyperhomocysteinemia, which may be secondary to folic acid deficiency[ 69 ], cerebral arterial vasculopathy, and antiphospholipid syndrome, a secondary autoimmune disorder[ 70 - 72 ]. Children with recurrent acute ischemic stroke should be screened for CD[ 73 ]. Because CD is a potentially treatable cause of cerebral vasculopathy and stroke[ 74 ], serology-specifically anti TTG antibodies should be included in the evaluation for cryptogenic stroke in childhood, even in the absence of typical gastrointestinal symptoms[ 72 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
“…The pathogenesis of stroke in CD youth may involve vitamin B12 deficiency[ 68 ] and possibly hyperhomocysteinemia, which may be secondary to folic acid deficiency[ 69 ], cerebral arterial vasculopathy, and antiphospholipid syndrome, a secondary autoimmune disorder[ 70 - 72 ]. Children with recurrent acute ischemic stroke should be screened for CD[ 73 ]. Because CD is a potentially treatable cause of cerebral vasculopathy and stroke[ 74 ], serology-specifically anti TTG antibodies should be included in the evaluation for cryptogenic stroke in childhood, even in the absence of typical gastrointestinal symptoms[ 72 ].…”
Section: Publication Summary Statisticsmentioning
confidence: 99%
“…Studies with large populations exploring the association between CD and pediatric stroke show a low incidence of AIS in CD children [12,13]. One study found that 2 out of 76 (2.26%) pediatric AIS patients and 2 out of 102 (1.96%) healthy children had positive serum tissue transglutaminase antibodies; this difference was not statistically significant [12].…”
Section: Discussionmentioning
confidence: 99%
“…One nationwide cohort study conducted in Sweden demonstrated that the excess risk of stroke in patients with CD was 24/100,000. Conversely, other research indicates little to no risk of AIS in pediatric patients with CD [12,13]. Therefore, this study aims to examine the incidence and outcomes of pediatric AIS patients with CD in a large nationwide sample.…”
Section: Introductionmentioning
confidence: 97%